Dietary Total Antioxidant Capacity is Inversely Associated with Prostate Cancer Aggressiveness in a Population-Based Study. (17th February 2016) - Vance, Terrence M.; Wang, Ying; Su, L. Joseph; Fontham, Elizabeth T. H.; Steck, Susan E.; Arab, Lenore; Bensen, Jeannette T.; Mohler, James L.; Chen, Ming-Hui; Chun, Ock K.
ABSTRACT: The purpose of this study was to determine the relationship between total antioxidant capacity (TAC) from diet and supplements and prostate cancer aggressiveness among 855 African Americans (AA) and 945 European Americans (EA) in the North Carolina–Louisiana Prostate Cancer Project (PCaP). Cases were classified as either high aggressive, low aggressive, or intermediate aggressive. TAC was calculated from the vitamin C equivalent antioxidant capacity of 42 antioxidants measured via food frequency questionnaire. EA reported greater dietary TAC from diet and supplements combined ( P < 0.0001). In both minimally and fully adjusted logistic regression models, TAC from diet and supplements combined was associated with a reduced odds of high aggressive prostate cancer in all men, AA and EA: odds ratios for highest vs. lowest level (>1500 vs. <500 mg vitamin C equivalent/day): 0.31 [95% confidence interval (CI): 0.15, 0.67; P -trend < 0.01], 0.28 (95% CI: 0.08, 0.96; P -trend < 0.001), and 0.36 (95% CI: 0.15, 0.86; P -trend = 0.58), respectively. These associations did not appear to differ between AA and EA. These data suggest that greater intake of antioxidants is associated with less aggressive prostate cancer. Additional research is needed to confirm these results and determine the underlying mechanisms.